A note comparing the welfare of Zebu cattle following three stunning-slaughter methods - Neves, J. E.G.; Paranhos da Costa, M. J.R. [UNESP]; Roça, R. O. [UNESP]; Faucitano, L.; Gregory, N. G. (Elsevier, 2016)
The objective of this study was to assess welfare of cattle during bleeding after slaughter with or without stunning. A total of 434 bulls were distributed across three slaughter treatments: penetrating captive bolt stunning followed by chest sticking (PCB, N = 279), non-penetrating captive bolt stunning followed by halal slaughter (NPCB, N = 67) and shechita without previous stunning (SHE, N = 88). Four measures of possible consciousness and return to sensibility were recorded 20 and 60 s after bleeding as welfare indicators. They were the frequencies of responses to nostril stimulation and tongue pinch, spontaneous eye blinking, and rhythmic breathing. All responses were absent in stunned cattle at both 20 and 60 s, and in SHE cattle 7, 4, 10, and 100% of the animals presented these responses, respectively. Repeat shots were required for 46% NPCB and 2% PCB (P < 0.05). The application of religious slaughter without previous stunning may result in greater risk of cattle suffering, pain and distress at slaughter.
Keywords: Cranial nerve reflexes; Non-penetrating captive bolt; Pain responses; Penetrating captive bolt; Shechita